Bihar Third Five-Year Plan Progress Report for the Period Ending March, 1962 - Planning Commission (Planning Commission, 1962)
This excludes Rs. 9.33.00 lakhs as Central share of Patratu extension and Central Scheme for D. V C. Excluding this amount of Ra. 9,33 lakhs. Rs. 70.62.00 lakhs has been shown in the State Plan.
Bihar